2006
DOI: 10.1111/j.1937-5956.2006.tb00250.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Competition on Recovery Strategies

Abstract: Manufacturers often face a choice of whether to recover the value in their end‐of‐life products through remanufacturing. In many cases, firms choose not to remanufacture, as they are (rightly) concerned that the remanufactured product will cannibalize sales of the higher‐margin new product. However, such a strategy may backfire for manufacturers operating in industries where their end‐of‐life products (cell phones, tires, computers, automotive parts, etc.) are attractive to third‐party remanufacturers, who may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
514
5
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 720 publications
(536 citation statements)
references
References 32 publications
13
514
5
4
Order By: Relevance
“…Such models were not considered in the methodology development as they usually reduce the observations to closed-loop supply chains therefore by default to closed-loop systems. Nevertheless, there are limitations to these approaches because Original Equipment Manufacturers have different options to deal with returns whereof one is the destruction of returned products [45,48]. In addition, market reality may work against integrated lifecycles.…”
Section: Closing Product Lifecycles With Cascade Utilizationmentioning
confidence: 99%
“…Such models were not considered in the methodology development as they usually reduce the observations to closed-loop supply chains therefore by default to closed-loop systems. Nevertheless, there are limitations to these approaches because Original Equipment Manufacturers have different options to deal with returns whereof one is the destruction of returned products [45,48]. In addition, market reality may work against integrated lifecycles.…”
Section: Closing Product Lifecycles With Cascade Utilizationmentioning
confidence: 99%
“…Moreover, the existence of large-scale grey recyclers increases the recycling cost of legitimate manufacturers, thereby impeding the latter from expanding their remanufacturing business. Manufacturers must invest huge funds to improve the remanufacturing system so that the adequate recyclable products can be acquired [18].…”
Section: State Of the Artmentioning
confidence: 99%
“…Hsu et al (2013) identified competition as a significant driver of GSCM. A proactive GSCM strategic planning can help a firm to gain competitive advantage (Ferguson and Toktay, 2006;Sarkis, 2003;Sharma and Vredenburg, 1998). Similarly, desire to achieve competitive advantage can act as a driver for GSCM (González-Benito and González-Benito, 2005;Rao and Holt 2005).…”
Section: Review On Gscm Enablersmentioning
confidence: 99%